The Upper Paleolithic of the Rio Maior basin (Portugal). Preliminary results of a 1987-1993 Portuguese-American research project - Zilhão, João; Marks, Anthony E.; Ferring, C. Reid; Bicho, Nuno F.; Figueiral, Isabel (Trabalhos de Antropologia e Etnologia, 2020)
.